Welcome to Westonci.ca, your go-to destination for finding answers to all your questions. Join our expert community today! Get quick and reliable solutions to your questions from a community of experienced experts on our platform. Our platform offers a seamless experience for finding reliable answers from a network of knowledgeable professionals.
Sagot :
To find [tex]\((f + g)(x)\)[/tex] when given the functions [tex]\(f(x) = 3^x + 10x\)[/tex] and [tex]\(g(x) = 5x - 3\)[/tex], we need to add these two functions together.
The combined function [tex]\((f + g)(x)\)[/tex] is given by [tex]\(f(x) + g(x)\)[/tex].
1. We start by writing down [tex]\(f(x)\)[/tex] and [tex]\(g(x)\)[/tex]:
[tex]\[ f(x) = 3^x + 10x \][/tex]
[tex]\[ g(x) = 5x - 3 \][/tex]
2. Next, we add [tex]\(f(x)\)[/tex] and [tex]\(g(x)\)[/tex]:
[tex]\[ (f + g)(x) = f(x) + g(x) \][/tex]
3. Substitute the expressions for [tex]\(f(x)\)[/tex] and [tex]\(g(x)\)[/tex] into this equation:
[tex]\[ (f + g)(x) = (3^x + 10x) + (5x - 3) \][/tex]
4. Combine like terms:
[tex]\[ (f + g)(x) = 3^x + 10x + 5x - 3 \][/tex]
[tex]\[ (f + g)(x) = 3^x + (10x + 5x) - 3 \][/tex]
[tex]\[ (f + g)(x) = 3^x + 15x - 3 \][/tex]
Therefore, the combined function [tex]\((f + g)(x)\)[/tex] is:
[tex]\[ (f + g)(x) = 3^x + 15x - 3 \][/tex]
Thus, the correct answer is:
A. [tex]\(3^x + 15x - 3\)[/tex].
The combined function [tex]\((f + g)(x)\)[/tex] is given by [tex]\(f(x) + g(x)\)[/tex].
1. We start by writing down [tex]\(f(x)\)[/tex] and [tex]\(g(x)\)[/tex]:
[tex]\[ f(x) = 3^x + 10x \][/tex]
[tex]\[ g(x) = 5x - 3 \][/tex]
2. Next, we add [tex]\(f(x)\)[/tex] and [tex]\(g(x)\)[/tex]:
[tex]\[ (f + g)(x) = f(x) + g(x) \][/tex]
3. Substitute the expressions for [tex]\(f(x)\)[/tex] and [tex]\(g(x)\)[/tex] into this equation:
[tex]\[ (f + g)(x) = (3^x + 10x) + (5x - 3) \][/tex]
4. Combine like terms:
[tex]\[ (f + g)(x) = 3^x + 10x + 5x - 3 \][/tex]
[tex]\[ (f + g)(x) = 3^x + (10x + 5x) - 3 \][/tex]
[tex]\[ (f + g)(x) = 3^x + 15x - 3 \][/tex]
Therefore, the combined function [tex]\((f + g)(x)\)[/tex] is:
[tex]\[ (f + g)(x) = 3^x + 15x - 3 \][/tex]
Thus, the correct answer is:
A. [tex]\(3^x + 15x - 3\)[/tex].
We appreciate your time. Please come back anytime for the latest information and answers to your questions. We appreciate your time. Please revisit us for more reliable answers to any questions you may have. Thank you for visiting Westonci.ca. Stay informed by coming back for more detailed answers.